The Relationship of Soil Types to the Dynamics of Groundwater Availability for Rice (Oryza sativa L.) and Corn (Zea mays L.) Plants in Pohuwato Regency - Dody Boy Venalocha Situmeang; Sukirman Rahim; Iswan Dunggio (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
The model for estimating groundwater availability for plants often overlooks the type of soil and the capacity of plants to absorb water from it. This study employs laboratory soil tests and statistical analyses to examine the relationship between various soil types in Pohuwato Regency and the variations in Groundwater Availability (KAT) levels for rice and corn plants. The results indicate that Andosol and Litosol are the soil types with the highest Field Capacity values in Pohuwato Regency, ranging from 331 mm to 403 mm. Meanwhile, Alluvial and Regosol soil types exhibit the lowest Permanent Wilting Point values in the Pohuwato Regency, ranging from 23 mm to 53 mm. The study results revealed a very high average correlation value of 0.907 between Field Capacity and the Permanent Wilting Point concerning the Groundwater Availability model. The research data, which includes soil characteristics and the Groundwater Availability model for rice and corn cultivation in Pohuwato Regency, can serve as a foundation for strategies that farmers can employ to enhance their future agricultural productivity.